The mediating role of organizational fairness in the relationship between toxic leadership and organizational trauma in education teachers of Yasouj city - Arvin, Neda; Tabari, Ahmad; Kork, Abdolrahim; Namjoo, Sajjad; Motaghed, Ata; Namjoo, Farhad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: Today’s organizations face wide challenges in the field of behavior and ethics among their members, and attention and solving them is considered an outstanding advantage for an organization. Toxic leaders (selfish people who do not care about the peace of their subordinates) can affect other behavioral variables of employees and their desire to express their opinions and beliefs or their moral courage. This research was conducted to determine the mediating role of organizational fairness in the relationship between toxic leadership and organizational trauma in employees of the Ministry of Education. Methodology: The design of the research was descriptive and structural equations type. All managers and official and unofficial employees of the Ministry of Education in 1401 formed the statistical population of the research. Among the statistical population, 260 people were selected and studied by simple random sampling. To collect data, the toxic leadership questionnaires of Schmidt (2000), and the Niehoff and Moorman organizational fairness questionnaire (1993). After collecting and extracting the data, the participants’ scores were analyzed using Pearson correlation and path analysis and statistical analysis software (SPSS). Results: The results showed a significant positive correlation between toxic leadership and organizational trauma and its subscales (0.01). There is a negative correlation between moral courage and organizational trauma (0.01). Conclusion: The results showed that organizational moral courage plays a significant mediating role in the relationship between toxic leadership and organizational trauma in the Ministry of Sports and Youth employees.